TRENDS IN THE DEVELOPMENT OF THE AVIATION VOCABULARY - Drobysheva, Natalia (Proceedings of National Aviation University (archive), 2019)
The article considers modern trends in the development of the terminology of the aviation industry, which were formed under the influence of linguistic and non-linguistic mechanisms. The purpose is to identify and analyze the general trend and features of the formation and prospects for the development of the terminology of the aviation industry. The tasks are to study the specific features of the origin, nature and state of the terminology of the given area of knowledge, to study the structural and word-building composition, the ways and characteristics of education, the role of international words and the harmonization of terms and terminology, and the definition of the educational (didactic) function of terms and terminology and teaching students terminology. Methods: Analyzing special vocabulary, the cognitive approach and the general linguistic principles of anthropocentrism, expansionism, neofunctionalism and explantoriness were used. Conclusions: Aviation vocabulary develops along the lines of general trends in scientific and technical terminology. The development of the terminology of the industry goes towards the complication of its structure and semantics, its ordering and systemic nature. The general trend of the economy of linguistic means for the modern period is manifested in the aviation terminology in an effort to compress the form of the term, and the form of the nomenclature terms is the most economical means for naming specific objects of the industry (particular notions). The main directions, prospects and tendencies of qualitative and quantitative growth of terms and their educational significance are shown.